Association between urinary phthalate levels and chronic pain in US adults, 1999–2004: A nationally representative survey - Jin, Guoping; Nie, Yaoyao; Fan, Jiayao; Yang, Ye; Chen, Dingwan; Li, Yingjun; Ju, Li (Frontiers in Neurology, 2023)
Introduction Chronic pain is a public health concern throughout the world. Ascertaining and managing its risk factors helps develop well-directed treatment plans and prevention strategies. Phthalates (PAEs) exposure leads to various health problems. The present study aims to explore the potential correlation between urinary PAEs metabolites and chronic pain in adults. Methods The study population data were extracted from the National Health and Nutrition Examination Survey (NHANES) conducted from 1999 to 2004 in the United States. Seven urinary PAEs metabolites were used to assess long-term PAEs exposure. The assessment of chronic pain was determined by a self-report questionnaire. Weighted analyses were conducted to consider the complex sampling design. Models were adjusted by demographic data and lifestyle factors. Urinary PAEs metabolites were assessed as both continuous and categorical variables. Tertile 1 was considered as the reference. Stratified analyses were performed by gender and pain site. All data analyses were conducted with STATA, version 15.1. P < 0.05 was considered with statistical significance. Results A total of 4,196 participants were considered in our final analysis. Chronic pain prevalence reached 52.19% (n = 2,138) among the participants, with women accounting for a large proportion (57.75% vs. 42.25%). After multivariable logistic regression analysis, a higher prevalence of chronic pain was observed among participants in the third tertile of mono-(2-ethyl)-hexyl phthalate (MEHP) (OR = 1.23, 95% CI = 1.02–1.48, P = 0.034) and mono-benzyl phthalate (MBzP) (OR = 1.28, 95% CI = 1.04–1.58, P = 0.022) in our adjusted model. The logtransformed concentration of MBzP also showed a significant association with chronic pain prevalence (OR = 1.09, 95% CI = 1.01–1.18, P = 0.036) in the adjusted model. In further analysis, the positive correlations of urinary phthalate metabolites with chronic pain remained robust when stratified by gender and chronic pain site. Conclusions Our findings presented a positive correlation between urinary PAEs metabolites and chronic pain among adult participants, and more causal research should be conducted to ascertain the interactions between the two and to expound their underlying mechanisms.